Relationship Between Parenting and Social Emotional Development of Children Aged 3-4 Years in Tenam Village, Muara Bulian District - Ririn Marinta; Syur'aini Syur'aini (Universitas Negeri Padang, 2023)
This research is motivated by the low social emotional development of children. This is evident from the fact that there are still a lot of kids who can't cooperate with friends, who don't want to share with friends, who want to win at all costs, and who are less receptive to their environment. This investigation will: 1) Take a look at the explanation of parental care for kids between the ages of 3-4 years. 2) See a summary of the social and emotional growth of kids between the ages of 3-4 years. 3) Seeing the relationship between parenting and social emotional development of children aged 3-4 years. This study's methodology is a quantitative, correlational technique. In this study, a total of 60 women with children in the age range of 3 to 4 years lived in Tenam Village, Muara Bulian District. Researchers frequently employ cluster random sampling. Strategies for gathering data in the form of a questionnaire. Techniques for data analysis use Product Moment and percentage calculations. The results of the study show that: 1) The description of parental care for children in Tenam Village is categorized as good. 2) The description of the social emotional development of children aged 3-4 years in Tenam Village is categorized as not good. 3) There is a relationship between parenting and social emotional development of children aged 3-4 years in Tenam Village.